Peranan BUMDES Bagi Petani Miskin di Desa Bangli Kecamatan Baturiti Kabupaten Tabanan - Trisnawati, Ni Putu Ayu Putri; Indrajaya, I Gusti Bagus (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 6, No. 6, Juni 2017 (pp. 920 - 1156), 2017)
ABTRACT Badan Usaha Milik Desa program is desperately needs by poor farmers households to increase agricultural products and farmers income in Bangli Village the District of Baturiti Tabanan Regency. The aims of this paper to review the influence of credit provided by Badan Usaha Milik Desa and labor influence to agricultural production and poor farmers income in the Bangli Village. With path analysis credit provided by Badan Usaha Milik Desa is no effect to agricultural production and poor farmer income in the Bangli Village, but labor is increase production poor farmers income in the Bangli Village. Badan Usaha Milik Desa located in Bangli Village and local government should be more often socialization and monitoring kind of users on credit from Badan Usaha Milik Desa.
Keywords: Keywords: BUMDES, credit, labor, production, income